2018
DOI: 10.30919/espub.es.180312
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Recovery of Copper Foil and Fabric from Waste Printed Circuit Boards by Decomposing Brominated Epoxy Resin Using Near Critical Water

Abstract: Waste printed circuit board (WPCB), a heterogeneous mixture of brominated epoxy resins (BERs), glass fibers and metals, has the challenge to separate and recover valuable materials. In this paper, an effective and benign near critical water (NCW) method was applied to decompose BERs to recover the glass fabric and metals. The effects of parameters including temperature, reaction time, feed ratio, acid-base catalyst, and size of WPCBs on the decomposition ratio of BERs were investigated. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…14 Also, it has been reported that near-critical water can be used to recycle printed circuit boards for the collection of copper foils and fabrics. 15 The overuse of printing equipment has led to a signicant increase in the number of waste toner cartridges. 16 Powdery waste toner (WT) accounts for 8.0 wt% of a toner cartridge.…”
Section: àmentioning
confidence: 99%
“…14 Also, it has been reported that near-critical water can be used to recycle printed circuit boards for the collection of copper foils and fabrics. 15 The overuse of printing equipment has led to a signicant increase in the number of waste toner cartridges. 16 Powdery waste toner (WT) accounts for 8.0 wt% of a toner cartridge.…”
Section: àmentioning
confidence: 99%
“…The rapid development of electronic and electrical equipment industry witnessed the increase of wasted electronic and electrical equipment (WEEE) plastics, whose annual output around the world reached 40 million tons according to the latest estimates . To some extent, traditional treatment of waste plastics will not only result in the waste of resources but also lead to environmental pollution . Fortunately, majority of WEEE plastics are still functional or slightly defective and thus can be reused for future life cycles .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the morphological and structural evolutions of WAIM–molded polyolefin parts in the presence of NAs as well as fillers are still unclear. Especially, the mutifunctions are desired to satisfy various applications including sensing, structural materials, energy, electromagnetic interference (EMI) shielding, environmental remediation, etc . Therefore, additional efforts have to be made to further investigate and improve the WAIM technology for producing various nanocomposite parts.…”
Section: Discussionmentioning
confidence: 99%